Pengaruh Model Project Based Learning Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Wahyuningsih, Anis; Hikmat, Ade (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study was to explore the interrelationship between the project-based learning model and student learning outcomes in Natural and Social Sciences (IPAS) subjects. The experiment was conducted on fourth grade students of SDN Baru 03 Pagi East Jakarta. Quantitative and quasi experimental methodologies were used as research methods. In addition, the sampling method is purposive sampling technique. Samples were taken from the control and experimental groups. 40 multiple choice questions were given for validity testing, with 30 questions considered valid and 10 questions considered failed. This study obtained the results in the IPAS lesson Ha accepted Ho rejected means that the project-based learning model has a significant effect on students of SDN Baru 03 Pagi East Jakarta is considered capable of improving student learning outcomes resulting in differences in the average post-test class of 75.2 in the experimental class and 89.8 in the control class.